Studies on Augmentation of Fracture Healing using Stem Cell Seeded on β-Tricalcium Phosphate in Goats - Kumar, Dharmendra; Bhargava, Mahesh Kumar; Shahi, Apra; Singh, Randhir; Tandia, Neelam; Singh, Priya (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
Twelve clinical cases of goats having long bone fracture, presented at College in Jabalpur (India), were included in the study. These animals  were randomly divided into two groups. Fracture segment of group I were immobilized by dynamic compression plate (DCP). In group  II fracture immobilization was done as in group I and the gap between the fracture segments was filled by bone marrow mesenchymal  stem cells (BMMSCs) seeded on β-tricalcium phosphates scaffold. Fracture healing was evaluated on the basis of inflammation, exudation,  pain, weight bearing and radiographic interpretation. Goat mesenchymal stem cells were established from bone marrow aspirates  under aseptic conditions. Fibroblast like appearance of MSCs was observed after 3-4 days of seeding. Early cessation of inflammation,  exudation and pain was observed in group II as compared to group I. Significant increase in weight bearing was observed from 7th day onwards in group II, while from 15th day onwards in group I. Complete weight bearing by all the goats was observed on 45th day  in group II and 90th day in group I. Radiographic interpretation on 7th post-operative day revealed periosteal reaction on the fractured  segment adjoining the fracture line in group II. On 30th post-operative day high density radiopaque area was visible at the fracture  site in group II. Radiograph of 45th day in group II revealed more organized periosteal as well as intercortical callus, which reduced on  60th day, indicative of initiation of remodeling. On 90th day, homogenous bone with patent bone marrow was observed, indicative of  completion of healing process in group II.
Keywords: β-tricalcium phosphate; Dynamic compression plate; Fracture; Radiograph; Stem cells; Weight bearing